Application of the Ultimum Remedium Principle in the Formulation of Legislation and Law Enforcement related to Banking Crimes - Laras Adysti Nariswari; Febby Mutiara Nelson (IHSA Institute, 2023)
Banking crime is a special external criminal law or administrative penal law which in law enforcement should adhere to the principle of ultimum remedium. However, there is an article in the Banking Law which reflects that criminal sanctions can still be imposed even though OJK has given administrative sanctions to perpetrators of banking crimes. Thus it can be interpreted that the article is not in line with the formulation of the Banking Law as an administrative penal law, which in law enforcement should prioritize the principle of ultimum remedium. Implementation of this article results in the emergence of disparities and can potentially cause problems in the law enforcement system. This article discuss how to apply the ultimum remedium principle in the process of handling banking crimes with the existence of the article that is not in line, by looking at the principles of banking crime as an economic crime, using normative research methodology. To avoid potential differences in interpretation regarding the implementation of Article 52, paragraph (1) of the Banking Law, the wording of those article can be amended to explicitly state that the Banking Law adheres to the principle of ultimum remedium in accordance with its specific nature.